2022
DOI: 10.1108/jiabr-07-2021-0192
|View full text |Cite
|
Sign up to set email alerts
|

The components of intellectual capital and organisational performance inwaqfinstitutions: evidence from Algeria based on structural equation modelling

Abstract: Purpose The purpose of this paper is to investigate the relationship between the sub-components of intellectual capital and organisational performance in waqf institutions in Algeria. Design/methodology/approach Data was collected through structured questionnaires from a sample of 193 waqf employees working in 23 different provinces in Algeria and analysed using partial least squares – structural equation modelling (PLS-SEM) software to test the path modelling and the relationship between the instruments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 106 publications
0
9
0
2
Order By: Relevance
“…Secondly, in a more precise manner, this study may extend auditing literature by explaining auditors’ responses to the different IC components (ICCs) independently if they are noticed. As it is extensively documented in the IC literature, the ICCs are expected to be valued by individuals differently, as they have various impacts on firm performance, mainly financial and organisational performance as the primary outcome of businesses (Laallam et al , 2022; Bataineh et al , 2022; Bansal et al , 2022; Agomor et al , 2022), as well as corporate social responsibility performance, as the secondary outcome of companies (Nirino et al , 2022; Tsai and Mutuc, 2020; Gallardo-Vázquez et al , 2019; Aras et al , 2011). Consequently, presenting detailed findings addressing the role of individual ICCs in a given company may suggest valuable managerial, practical and social implications.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, in a more precise manner, this study may extend auditing literature by explaining auditors’ responses to the different IC components (ICCs) independently if they are noticed. As it is extensively documented in the IC literature, the ICCs are expected to be valued by individuals differently, as they have various impacts on firm performance, mainly financial and organisational performance as the primary outcome of businesses (Laallam et al , 2022; Bataineh et al , 2022; Bansal et al , 2022; Agomor et al , 2022), as well as corporate social responsibility performance, as the secondary outcome of companies (Nirino et al , 2022; Tsai and Mutuc, 2020; Gallardo-Vázquez et al , 2019; Aras et al , 2011). Consequently, presenting detailed findings addressing the role of individual ICCs in a given company may suggest valuable managerial, practical and social implications.…”
Section: Introductionmentioning
confidence: 99%
“…Hal itu bisa dilakukan dengan melaporkan laporan keuangan melalui media internet karena jangkauan informasi yang luas dan murah (Anggita et al, 2021;Basuony & Mohamed, 2014;Hanafiyah & Suprayogi, 2020;Rini, 2016). Bahkan menurut Laallam et. al.…”
Section: Kajian Literatur Transparansi Melalui Internet Financial Rep...unclassified
“…DD juga berupaya meningkatkan kompetensinya baik dari segi kemampuan sumber daya manusia maupun sistem teknologinya. Sebab, modal teknologi akan membantu meningkatkan transparansi (Laallam et al, 2022). Oleh karenanya, kesadaran pengelola DD atas kewajiban transparansi harus terpenuhi.…”
Section: Prinsip Tanggung Jawab Untuk Mengatasi Hambatan Transparansiunclassified
“…Furthermore, religiosity affects entrepreneurial intention (Fikrianoor et al , 2021), entrepreneurial motivation (Acheampong, 2017; van der Westhuizen and Adelakun, 2021) and entrepreneurial self-efficacy (Charzyńska et al , 2021). Islam is believed to build human capital and social capital within a country (Laallam et al , 2022). Junaidi (2022) also suggested that religiosity affects Muslim attitudes and commitment.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%